Perbandingan Metode Ekstraksi terhadap Kadar Flavonoid dan Aktivitas Antioksidan Ekstrak Etanol Daun Pulai (Alstonia scholaris) dengan Metode 2,2-difenil-1-pikrilhidrazil (DPPH) - Wahyuningsih, Sri; Sari, Nur Indah; Wahid, Hilmiati; Azima, Azima (Sinteza, 2026)
Pulai leaves (Alstonia scholaris) are known to contain various secondary metabolites such as flavonoids, so the choice of extraction method is a factor that affects the quality and quantity of bioactive compounds produced. This study aims to compare the total flavonoid content and antioxidant activity of ethanol extracts of pulai leaves obtained through two different extraction methods, namely maceration and reflux. This study is a laboratory experimental study using 96% ethanol solvent in both extraction methods. The flavonoid content was determined quantitatively using UV-Vis spectrophotometry with quercetin as the standard. The antioxidant activity test was performed using the 2,2-diphenyl-1-picrylhydrazil (DPPH) method based on the IC50 value. The results showed that the extract obtained using the reflux method had a higher flavonoid content of 17.11±0.03 mgQE/g and an IC50 value of 7.84±0.02 ppm, while the maceration method produced a flavonoid content of 8.42±0.02 mgQE/g and an IC50 value of 12.53±0.17 ppm. As a positive control, vitamin C had an IC50 value of 5.26±0.08 ppm. Based on these results, the extraction of pulai leaves (Alstonia scholaris) using the reflux method proved to be more effective in extracting flavonoid compounds and had higher antioxidant activity compared to the maceration method.